Stratification of metal and sulphate loads in acid mine drainage receiving water dams - variables regionalization by cluster analysis - Grande, J. A. (2015)
The Sancho Reservoir (Iberian Pyrite Belt, SW Spain) is nourished by the waters of the river Meca, which is affected by acid mine drainage (AMD) processes from the abandoned Tharsis mine. The aim of the present work is to study the hydrochemical variations in this reservoir, in order to define potential stratification processes in metal load and sulphates. A stratified sampling from the surface, with one meter deep intervals to the bottom of the dam, was performed. The results show a clear stratification of temperature, pH, electric conductivity, dissolved oxygen, metal and sulphate loads associated with depth. There is an increase of metal loads at the bottom of the reservoir, though previous studies only detect iron. The proximity between pH and aluminium suggests that water chemistry is strongly influenced by aluminium precipitation processes. This indicates the buffer effect that aluminium exercises, which precipitates as amorphous or low crystalline phases, introducing hydrogen ions to the system, while alkalinity input tends to raise pH.